Pro-Environmental Health Behavior (PEHB): A Contextual Behavior of Elementary Students in Biology Learning - Ichsan, Ilmi Zajuli; Susanti, Rosa; Merliana, Anggit; Marhento, Giry (Attractive : Innovative Education Journal, 2022)
Education plays a significant role to overcome the low Pro-Environmental Health Behavior (PEHB). By and large, PEHB can be defined as a behavior that supports the achievement of a healthy environment. The study aims to describe the PEHB profile of elementary school students in biology learning. The research method used is a descriptive method with a survey as the data collection technique. The number of items in the PEHB instruments employed in the research consists of 12 items, which are the explanation of 6 PEHB indicators. The indicators are (1) The utilization of energy that supports environmental health; (2) Environmental health-oriented transportation; (3) Waste management to sustain environmental health; (4) Environmental health concept-based consumption; (5) Recycle toward a healthy environment; and (6) Social participation to establish a healthy environment. The research results indicate that the average score of the elementary school students’ PEHB is 67.85 (Moderate). The indicator with the lowest average score is those related to recycling. Moreover, the highest average score is in the first indicator that is related to the utilization of energy. The research concludes that the PEHB score of elementary school students is in a moderate category. A suggestion for future research is related to the development of biology learning media concerning environmental health. Keywords: Biology Learning, Contextual Behavior, Pro-Environmental Health Behavior